The influence of impurity ions of transition metals on radiation induced prosseces - Baltabekov, A.S.; Koketaitegi, T.A.; Kim, L.M. (Ye.A.Buketov Karaganda State University Publishing house, 2010)
In work results of research of monocrystals of potassium sulphate are resulted. Pure of potassium sulphate, and also of potassium sulphate doped have been investigated by ions of cobalt, manganese and nickel. Optical measurements were carried out by a photo-electric method, by a standard technique with the help SPh-16. Researches have shown, that accumulation lightsum in pique TL at 280-300К goes in the doped crystal faster, than in a pique recombination luminescence with a maximum at 190К. We know, that as a result of an irradiation in x-ray quantums there is a change of a charging condition impurity ion of copper. It is shown, that influence to radiation leads to reduction of optical density in impurity strips of absorption. Authors of work give this a unique explanation: there is a change of a charging condition at initial ions of bivalent transitive metals, that is there is a formation of ions Ме+ or Ме3+.
Keywords: monocrystals; photo-electric method; accumulation lightsum; recombination luminescence; doped crystal faster